The European Union in International Fora: Lessons for the Union's External Representation after Lisbon - Lieb, Julia, M.E.S.; Ondarza, Nicolai von, M.A.; Schwarzer, Daniela, M.A. (Nomos Verlagsgesellschaft mbH & Co. KG, 2011)
Due to the hereditary fragmentation of its external representation, the European Union’s structures and procedures for international action differ significantly across policy fields. Reforms aiming at improved coherence have primarily concerned traditional areas of foreign and security policy. This edited volume studies the EU’s external action in a broader spectrum of policy fields such as energy and climate, trade, economics and finance as well as labour and social policy.The book contributes to the present discussion on the development of the external action of the EU after the institutional reforms introduced by the Lisbon Treaty. In analysing structures and procedures of external representation in selected policy fields with diverging degrees of integration, the volume explores the advantages and drawbacks of their specific models of external action. The contributing academics and practitioners reveal a clear challenge for the EU to improve the coherence, efficiency and legitimacy of a joint representation of interests in order to become a more relevant actor in the rapidly changing international environment.With contributions by:Sami Andoura, Gisbert Brinkmann, Rudi Delarue, Gabriel Glöckler, Julia Lieb, Nicolai von Ondarza, Jan Orbie, Bregt Saenen, Simon Schunz, Daniela Schwarzer, Zbigniew Truchlewski, Antonio Villafranca, Clara Weinhardt and Stephen Woolcock.